2012
DOI: 10.1111/j.1472-765x.2012.03308.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel Fe(II)/α-ketoglutarate-dependent dioxygenase fromBurkholderia ambifariahas β-hydroxylating activity ofN-succinyl l-leucine

Abstract: An Fe(II)/α‐ketoglutarate‐dependent dioxygenase, SadA, was obtained from Burkholderia ambifaria AMMD and heterologously expressed in Escherichia coli. Purified recombinant SadA had catalytic activity towards several N‐substituted l‐amino acids, which was especially strong with N‐succinyl l‐leucine. With the NMR and LC‐MS analysis, SadA converted N‐succinyl l‐leucine into N‐succinyl l‐threo‐β‐hydroxyleucine with >99% diastereoselectivity. SadA is the first enzyme catalysing β‐hydroxylation of aliphatic amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…Moreover, the addition of ferrous iron, ␣KG, and ascorbate to the reaction mixture was required for the maximum activity of the F. oxysporum c8D cell lysate. Since similar observations have been made for other amino acid hydroxylases belonging to the Fe/␣KG-DO superfamily (19)(20)(21), these results suggest that the enzyme responsible for L-Pip-hydroxylating activity belongs to the Fe/␣KG-DO superfamily.…”
Section: Resultssupporting
confidence: 57%
“…Moreover, the addition of ferrous iron, ␣KG, and ascorbate to the reaction mixture was required for the maximum activity of the F. oxysporum c8D cell lysate. Since similar observations have been made for other amino acid hydroxylases belonging to the Fe/␣KG-DO superfamily (19)(20)(21), these results suggest that the enzyme responsible for L-Pip-hydroxylating activity belongs to the Fe/␣KG-DO superfamily.…”
Section: Resultssupporting
confidence: 57%
“…Five kinds of substrates-N-succinyl-L-leucine (NSLeu), N-succinyl-L-valine (NSVal), N-succinyl-L-isoleucine (NSIle), N-succinyl-Lphenylalanine (NSPhe) and NSDOPA-were synthesized as described previously [13]. The reaction proceeded at 30°C for 2 h and the reaction mixture was composed of 10 mM substrate, 15 mM a-KG, 0.5 mM FeSO 4 Á7H 2 O, 10 mM L-ascorbate, 50 mM Tris-HCl buffer (pH 8.0), and 1 mg ml À1 purified SadA.…”
Section: Activity Assaymentioning
confidence: 99%
“…In previous studies, we have reported an Fe(II)-and a-ketoglutarate (KG)-dependent dioxygenase from Burkholderia ambifaria AMMD (SadA, 30,664 Da) [13,14]. SadA enantioselectively catalyzes the C3-hydroxylation of not only N-succinyl branched-chain L-amino acids but also N-succinyl aromatic L-amino acids to produce the hydroxy amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is useful as a novel biocatalyst for the ( R )-selective hydroxylation at the C-3 position of N -substituted branched-chain L-amino acids, especially N -succinyl-L-leucine (NSLeu), to produce N -succinyl-(2 S ,3 R )-3-hydroxyleucine (NSHLeu) with >99% stereoselectivity (Fig. 1) [10]. (2 S ,3 R )-3-hydroxyleucine is a promising material for the preparation of certain cyclic depsipeptides which function as platelet aggregation inhibitors and is also a component of the antibiotic lysobactin [11], [12].…”
Section: Introductionmentioning
confidence: 99%